Habituasi Nilai Religius Melalui Kearifan Lokal: Pelajaran dari Adat Kapena Desa Rindiwawo Nusa Tenggara Timur - Mubarok, Zais (Lembaga Sosial Rumah Indonesia, 2023)
This research aims to find out the habituation of religious values in the context of local wisdom. This research is field research with the type of qualitative research in which it describes the habituation of religious values through Adat Kapena Nusa Tenggara Timur. Techniques to collect data through observation, documentation, and interviews, while data analysis techniques use the Miles and Huberman models, which consist of data collection, data reduction, data presentation, and data verification. The results of the study show that religious values are increasingly awakened, as seen from activities for 4 days, changing old habits to be more positive, such as being willing to take part in recitations, reading the Koran, increasing prayer services, and continuing dzikir together. This sift begins to grow because they state that they are very concerned about old habits that are not useful activities, such as gambling, cockfighting, and gathering without any benefits from them. The form of respecting local wisdom is still maintained; it’s just that habituation activities begin to experience the transition of old habits into religious values that develop in society.